(untitled) (Journal of Environmental Science and Natural Resources, 2016)
Salinity is a limiting factor for growth and development, since it affects several physiological processes in plants. An experiment was conducted to evaluate rice yield and quality of soil using different organic and inorganic amendments. Field experiment was laid out in a randomized block design with three replications and six treatments. Each treatment was received recommended doses of chemical fertilizers also. Based on these results, 50% of rice straw and gypsum amendments could be recommended to mitigate soil salinity thereby, improving the crop productivity of the salt affected lands. Maximum plant height, panicle length, total and effective tillers per hill and filled grains per panicle were observed in 50% (rice straw + gypsum) treated plots. Nutrients uptake were increased in grain and straw using different treatments compared to control and rice straw alone treated plots. In post harvest soil, there was a slight change of salinity and pH as affected by different treatments. Addition of rice straw and gypsum showed positive impact on organic carbon in soil. J. Environ. Sci. & Natural Resources, 8(2): 109-113 2015